Glycans in diseases and therapeutics - Paväo, Mauro S. G. (Biology of extracellular matrix., 2011)
Initially believed to be inactive molecules, glycans are now considered essential for life, both under normal and pathological conditions. This volume of the series ?Biology of Extracellular Matrix? reviews the most recent findings on the role of glycans in the development of diseases and the possible therapeutic use of this class of molecules. It shows how the interaction of glycans with growth factors, growth factor binding proteins, extracellular proteases, protease inhibitors, chemokines, morphogens, and adhesive proteins regulates inflammation, infection, cancer, atherosclerosis, thrombosis and embryonic stem cell biology. Furthermore, an extensive survey about the structure and pharmacological effects of unique marine glycosaminoglycans is discussed as well as the possibility of using these glycans as therapeutic agents. The series Biology of Extracellular Matrix is published in collaboration with the American Society for Matrix Biology. The series Biology of Extracellular Matrix is published in collaboration with the American Society for Matrix Biology.